2016
DOI: 10.1089/ars.2015.6331
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Mediates the Antioxidant Effect of Hydrogen Sulfide in Endothelial Cells

Abstract: H2S enhances AP-1 binding activity with the SIRT3 promoter, thereby upregulating SIRT3 expression and ultimately reducing oxidant-provoked vascular endothelial dysfunction. Antioxid. Redox Signal. 24, 329-343.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 54 publications
5
54
0
Order By: Relevance
“…Treatment with NaHS enhanced the SIRT1 deacetylase activity in human umbilical vein endothelial cells [119, 121]. In addition, increases in the expression of SIRT1 [119, 120], SIRT3 [180, 192] and SIRT6 [180, 193] were shown after treatment with H 2 S.…”
Section: Hydrogen Sulfide and Agingmentioning
confidence: 99%
“…Treatment with NaHS enhanced the SIRT1 deacetylase activity in human umbilical vein endothelial cells [119, 121]. In addition, increases in the expression of SIRT1 [119, 120], SIRT3 [180, 192] and SIRT6 [180, 193] were shown after treatment with H 2 S.…”
Section: Hydrogen Sulfide and Agingmentioning
confidence: 99%
“…Zhao et al examined the vasoactive effects of H 2 S in rat aortic tissues [63][64][65][66][67][68][69][70]. The report shows a dose-dependent inhibition of H 2 S-induced vasodilation of rat aortic rings by the K ATP channel inhibitor, glibenclamide.…”
Section: Vasodilationmentioning
confidence: 99%
“…Thus, the synthesis of this gasotransmitter is not completely defined and remains an area of active investigation as discussed below. After synthesis and release, H 2 S has effects in the vascular wall that include inhibition of inflammation [13][14][15][16][17], stimulation of angiogenesis [18][19][20][21][22], increased production of endothelium-derived relaxing factors [23][24][25], activation of antioxidant pathways [26], and direct stimulation of vascular smooth muscle cell vasodilation [8,27,28]. These pathways will be discussed below along with a discussion of H 2 S production and activity in several cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Besides HUVECs, previous studies from our group demonstrated that H 2 S increased SIRT1 expression to abolish the oxidative stress induced apoptosis in H9c2 cardiomyocytes [70] and previous studies from our group demonstrated [6] found that H 2 S attenuated inflammatory hepcidin partially by promoting SIRT1-mediated STAT3 deacetylation. SIRT3, one of the isoforms of SIRT family, has also been reported that it could be regulated by H 2 S to protect endothelial cells in an antioxidant manner [71]. …”
Section: H2s Epigenetic Regulation Atherosclerosis Is An Important Famentioning
confidence: 99%